2013
DOI: 10.1136/vr.101598
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of mastitis pathogens by real‐time PCR compared to bacterial culture

Abstract: Rapid and accurate identification of mastitis pathogens is important for disease control. Bacterial culture and isolate identification is considered the gold-standard in mastitis diagnosis but is time-consuming and results in many culture-negative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
4
25
1
1
Order By: Relevance
“…Our findings showed that both tests are equally highly specific for detection of CNS from milk, whereas qPCR has a higher Se than BC at all the tested cut‐offs for qPCR and BC. This is consistent with previous studies, which found that PCR shows a higher Se than BC for detecting bacteria in milk samples (Taponen et al ; Shome et al ; Keane et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that both tests are equally highly specific for detection of CNS from milk, whereas qPCR has a higher Se than BC at all the tested cut‐offs for qPCR and BC. This is consistent with previous studies, which found that PCR shows a higher Se than BC for detecting bacteria in milk samples (Taponen et al ; Shome et al ; Keane et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Shome et al 2011;Keane et al 2013).TheSe and Sp estimates of qPCR (94 and 77%) are comparable with estimates of Nyman et al (2016),…”
supporting
confidence: 68%
“…This phenomenon did not seem to play an important role in the current study of ovine milk, possibly due to the fact that samples were from clinically healthy animals and to the short delay between sampling and culturing. Another explanation for real-time-PCR-positive, culture-negative results is higher sensitivity of real-time PCR compared with culture (Cederlöf et al, 2012;Keane et al, 2013). The number of positive samples in our study was too small for meaningful analysis of the comparative sensitivity and specificity of real-time PCR and culture.…”
Section: Discussionmentioning
confidence: 72%
“…The same interpretation system could be applied also in PCR diagnostics [31]. In general, PCR testing has proven to be a fast, sensitive and reliable test suitable for routine mastitis bacteriology [24, 28, 32]. An advantage of the PCR test is the comprehensive panel of pathogens, and uniform procedure and interpretation, in contrast to bacteriological culturing, where performance and procedures of laboratories may differ [33].…”
Section: Discussionmentioning
confidence: 99%